The role of nuclear chemistry and radiochemistry in nanosafety studies. Issue 11 (2nd December 2019) - Groppi, Flavia; Sabbioni, Enrico; Manenti, Simone
ABSTRACT: Nowadays there is an increasing demand of engineering nanoparticles – ENPs – thanking the excellent characteristics and properties of the products in which nanoparticles (NPs) are used. On the other hand, many are the unresolved questions about their potential adverse health and environmental impacts arising from exposure to these innovative materials. The growing utilisation of ENPs in consumer and industrial products have led to a potential increase of human exposure, thus raising concerns of many scientists and governments regarding health risks to workers and the public. Research on the impact of ENPs is strongly hampered by a lack of reliable tools to detect, visualise, and quantitatively trace particles movement and transfer in complex environmental and biological systems. The research tries to give some answers in this field using many different analytical techniques. In this paper, the types of information that can be obtained using nuclear techniques will be presented, with some examples of applications related to studies with metallic NPs.